Practices of Gender-Responsive Budgeting in Nepal - Koirala, Padma (Bouddhik Abhiyan (बौद्धिक अभियान), 2023)
This paper attempts to analyze gender-responsive budgeting (GRB) practices in Nepal. Gender-responsive budgeting (GRB) is an approach to budgeting that uses an interrelated gender lens to respond to the diverse experiences of gender-diverse groups. This budgeting is also known as gender budgeting. This paper is based on descriptive research design and mixed research methods as well as secondary. Secondary data were collected from the reviews of Gender Responsive Budgeting reports and articles. Both archives and digital sources were used to search review materials. The findings of this paper show that GRB is a fiscal policy or administration that is used for promoting gender equality for girls and women. It provides a tangible framework for mobilizing budgets through a wide range of actors to address the gender-diﬀerentiated gaps to achieve desirable gender equality outcomes. Indeed, GRB can enter any stage of the budget cycle by identifying the prominent efforts. This paper concludes that gender issues became at the center of inclusive development since ancient times in Nepal. The fiscal policy tries to address GRB from2007/08 with progressive efforts, although the implementation of GRB faces a lot of challenges and barriers to achieving desirable outcomes. Despite this, the international community has recognized the effort of Nepal as a prominent GRB process.